Drug prevention campaigns directed at university youth: a field study in the Emirate of Sharjah - Al-Marashda, Saleh; AL-Taii, Alaa (Al-Adab Journal, 2025)
The current study aimed to identify the extent to which drug prevention campaigns offered to university youth in the Emirate of Sharjah follow international standards for drug prevention, and to identify this evaluation according to the variables (gender, specialization) and how these campaigns can be developed. To achieve the objectives of the study, a questionnaire was prepared based on the theory of control. Social survey, which was applied to a stratified random sample consisting of University of Sharjah students, using the sample social survey approach. The results indicated that the campaigns presented to university youth follow international standards for drug prevention when they are designed, and there is a difference between males and females in their evaluation of the campaigns, and there is no difference regarding specialization. The study recommended intensifying the campaigns and diversifying their methods because of their effectiveness in reducing the dangers of drugs.